Pengaruh Harga, Kualitas Produk dan Desain Produk Terhadap Keputusan Pembelian Kain Jumputan Rumah Produksi Cahaya Jumputan Tuan Kentang Palembang - Rusmianita; Roswaty; Emilda (Universitas Indo Global Mandiri, 2023)
This study aims to determine the effect of price, product quality and product design on purchasing decisions. Using quantitative analysis techniques using SPSS 25. The population in this study were all consumers who bought jumputan fabric at Cahaya Jumputan Production House, Tuan Kentang Palembang, namely 486 consumers for one year. The number of samples taken is at least 5 times the number of indicators used in the study. In this study there were 23 question items, so the minimum sample size needed was 23 x 5 = 115 samples, data analysis using SPSS 25. The results of this study concluded that the price variable had a positive and significant effect on purchasing decisions asevidenced by the Sig value of 0.000 <0.05, Product quality variables have a positive and significant effect on purchasing decisions with a Sig value of 0.004 <0.05, product design variables have a positive and significant effect on purchasing decisions with a Sig value of 0.000 <0.05, price variables, product quality and product design simultaneously have a positive and significant effect on purchasing decisions with a Sig value of 0.000 <0.05. The results of testing the correlation coefficient (R) obtained a value of 0.563. this shows that the level of relationship between the price, product quality and product design variables on purchasing decisions is moderate (56.3%) and the results of the study using the coefficient of determination (R2) test obtained a value of 0.316. This shows the magnitude of the contribution between the price, product quality and product design variables can explain the purchasing decision variable by 31.6%, the remaining 68.4% can be explained or influenced by other variables not included in this study.Keywords: Price, Product Quality, Product Design, Purchase Decision